The Influence of the Tide Levels on the Water Electrical Conductivity Parameter in the Estuary Area: In-Site and Real-Time Measurement - Alaydrus, Alfina Taurida; Budianto, Arif; Rahayu, Susi; Andini, Mira; Akhyar, Halil; Anggriani, Ni Ketut (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
One area that requires attention in water quality studies is the estuarine ecosystem. Estuaries are transition zones connecting freshwater and marine waters, thus possessing unique environmental dynamics. However, there is limited information regarding the effect of sea tides in the area on local estuary water quality. Therefore, this study aims to identify the existing relationship between sea tide levels and EC values, using an IoT-based system that is portable, lightweight, and capable of operating in real time. This study was conducted over five days in Senggigi village, Batulayar, West Nusa Tenggara, Indonesia. The collected data focused on the EC parameter's water quality levels at different tide levels, which were monitored using the self-developed system. This system was developed using an EC sensor, a microcontroller, and a wireless internet router (for wireless data communication via ThingSpeak.com). This system was also equipped with a pH sensor, a TDS sensor, and a water temperature sensor. The recorded data show that the resulting data are valid and highly accurate, and that the system is ready for examination at the measurement area. The resulting data show that the correlation between tide level and EC value is logarithmic, with a regression coefficient of 0.934. The EC level was about 20.42 – 62.54 mS/cm, depending on the tide level. It can be concluded that the tide level indeed influences the EC parameter in the estuary area. Moreover, TDS plays an important role in regulating EC levels, underscoring the need to systematically measure this parameter in any estuarine water-quality study.